Assessing distribution changes of selected native and alien invasive plant species under changing climatic conditions in Nyeri County, Kenya. - Julius Maina Waititu; Charles Ndegwa Mundia; Arthur W Sichangi (PLoS ONE, 2022)
The role of climate change in enhancing bio-invasions in natural environments needs to be assessed to provide baseline information for effective species management and policy formulations. In this study, potential habitat suitability maps were generated through Ecological Niche Modeling for five problematic alien and native species in current and future climate simulations for the periods 2050s and 2070s under RCP2.6, RCP4.5, and RCP8.5 emission scenarios. Projected current binary suitability maps showed that 67%, 40%, 28%, 68%, and 54% of the total study area ~ 3318 Km2 is suitable for C. decapetala, L. camara, O. stricta, S. didymobotrya and S. campylacanthum species, respectively. Assuming unlimited species dispersal, two of these species, C. decapetala and S. didymobotrya, were observed to have consistent gradual increase in potential habitats and no habitat losses under the three RCPs by the end of the 2050 and 2070 future periods. The highest recorded relative potential habitat increase was observed for O. stricta at ~205% under RCP2.6 and ~223% under RCP8.5. Although L. camara and O. stricta were observed to have habitat losses, the losses will be very low as compared to that of S. campylacanthum. L. camara and O. stricta relative habitat losses were predicted to be between ~1% under RCP2.6 to ~4.5% under RCP8.5 by 2070 while that of S. campylacanthum was between ~50% under RCP2.6 to ~68% under RCP8.5 by the year 2070. From this study we conclude that the target study species are expected to remain a big threat to inhabited areas as well as biodiversity hotspot areas especially in the Mt. Kenya and the Aberdare forest and national park reserves under climate change. The information generated through this study can be used to inform policy on prioritizing management of these species and subsequent determination of their absolute distributions within the area.